(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
Debates on the morality of lottery generally intermingle with weak public funds. Post-revolutionary governments have had diferent views on gambling companies. In the history of public lottery companies in Mexico, we address decision-making processes and conlicts of interest between civil servants and prominent businesspeople which can be observed both on the level of the state and federal governments, as well as between public organizations seeking to gain control over lotteries. his paper looks into the discursive use of social issues and the promise of pushing the beneits as a way to legitimate the game in front of the state. hrough a novel source study of the archives of the Lottery, an analysis is provided of the very complex set of norms and those illegal agreements which strengthened state control by adjusting interests, thus generating a signiicant money low between 1915 and 1933.